2008
DOI: 10.1542/peds.2008-0292
|View full text |Cite
|
Sign up to set email alerts
|

At What Age Do Children Start Taking Daily Asthma Medicines on Their Own?

Abstract: Clinicians may need to screen for child daily controller-medication management and include even young children when educating families on the use of asthma medications and other key asthma-management tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(122 citation statements)
references
References 20 publications
5
116
0
1
Order By: Relevance
“…In this stage it is very important that parents learn to give their children more autonomy in managing their asthma [39]. According to OrrellValente et al [40] children at the age of 11 take on average 50% of the responsibility of their medication intake. This percentage increases to approximately 75% by the age of 15 and 100% by the age of 19.…”
Section: Societal Perspective: Role Of Peersmentioning
confidence: 99%
“…In this stage it is very important that parents learn to give their children more autonomy in managing their asthma [39]. According to OrrellValente et al [40] children at the age of 11 take on average 50% of the responsibility of their medication intake. This percentage increases to approximately 75% by the age of 15 and 100% by the age of 19.…”
Section: Societal Perspective: Role Of Peersmentioning
confidence: 99%
“…13,14 Poor adherence in adolescents may be related to not understanding or not perceiving the benefi ts of the treatment, wanting to conform to peers, and rebelling against authority.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…[9][10][11][12] CPAP adherence patterns of adolescents have not been extensively studied, but studies of medication adherence in other adolescent groups, such as asthmatics, epileptics, and diabetics have demonstrated poor adherence. 13,14 Poor adherence in adolescents may be related to not understanding or not perceiving the benefi ts of the treatment, wanting to conform to peers, and rebelling against authority. 15 In addition, adolescents may have little parental supervision of CPAP use.…”
mentioning
confidence: 99%
“…We divided age of child into 3 categories (ages 4-7, ages 8-12, and ages 13-19) based on the age at which children tended to start administering their own medications in our data set 22 and the age of adolescence because previous studies have revealed decreased adherence during adolescence. [23][24][25] We dichotomized caregiver age into 2 categories, 28 to 42 years old and 43 to 59 years old based on the distribution of ages in our data set.…”
Section: Variablesmentioning
confidence: 99%